PENEGAKAN HUKUM PIDANA TERHADAP PENCEMARAN LIMBAH CAIR PABRIK DI KABUPATEN KUANTAN SINGINGI BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Munthe, Henry Haro; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Pollution is entered or the inclusion of living creatures, substances, eneergi, and / or other components into the environment by human activities that exceed the environmental quality standards have been set. Waste is the residue of a business and / or activities. Pollution of palm oil mill effluent in KuantanSingingiare offenses that have a negative impact on the environment, public morality and so forth. Therefore, law enforcement agencies Regency Kuantan Singingi attempt to eradicate or resolve criminal offense the mill effluent pollution. But enforcement of the law by the Law Enforcement Institutions Kuantan Singingi not operating effectively and efficiently. This is evident from the increasing number of data streams polluted water from 2014 to 2015. Of the many cases of contamination of wastewater in KuantanSingingi no criminal sanctions in accordance with article 98 of Law No. 32 of 2009 on the Protection and Environmental Management. The purpose of writing the thesis as follows: first, to determine the criminal enforcement against palm oil companies that dump waste into the Watershed, second, to determine the barriers and efforts faced by law enforcement officials in enforcing the law against oil palm companies that dump waste into Watershed River.This type of research can be classified in this type of sociological research, ie research on the location or point directly studied, this study conducted at the Department of the Environment Agency and the Singingi Regency Kuantan in Kuantan District Police Singingi, ie the correlation between legal research with the public.From the research there are two things that can be inferred. First, the implementation of law enforcement against pollution of wastewater plant in Kuantan Singingi not been effectively proven the growing number of actors existing wastewater pollution in Kuantan Singingi. The second obstacle encountered in the implementation of law enforcement against pollution of wastewater is less awareness among the legal community, the law enforcement less proportional and lack of facilities and infrastructure. Efforts are being made to enforce waste pollution include with Regency Kuantan Resort Police Singingi, extension with the community, Establish good relationships with the community. Suggestions author, the first criminal enforcement against environmental pollution of the watershed caused by liquid waste palm oil factory in Kuantan Singingi to be maximized in view of the increasingly widespread pollution of wastewater, both for the Environment Agency in order to be again increased surveillance for no longer pollution in Kuantan Singingi.Keywords: Law Enforcement-Pollution Wastewater Plant